PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI TRANSPORTASI DAN PENGAMANAN PADA BADAN PEMERIKSA KEUANGAN JAKARTA PUSAT - Tri Astuti Nurbayani, Tia; Syawaludin (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the effect of training and work discipline on the performance of Transportation and Security employees at the Central Jakarta Supreme Audit Agency. The method used is quantitative. The sampling technique used saturated sampling and a sample of 54 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that training has a significant effect on employee performance with a regression equation value of Y = 16,826 + 0.571 The value of determination or contribution of influence is 0.675 or 67.5% while the remaining 32.5% is influenced by other factors. Hypothesis testing obtained a calculated t value > t table or (6.593 > 2.007. Work discipline has a significant effect on employee performance by obtaining a regression equation value of Y = 6.455 + 0.796 or the contribution of influence is 67.7% or 32.3% while the remaining 61.5% is influenced by other factors. The hypothesis test shows that the calculated t value is > t table or (2.993 > 2.007). on employee performance with the regression equation Y = 13.277 + 0.332X1 + 0.341X2. The correlation coefficient value or level of relationship between the independent variable and the dependent variable is 0.799, meaning it has a strong relationship. while the remaining 46.3% was influenced by other factors. Hypothesis testing obtained a calculated F value > Ftable or (29.544 > 2.790).